Characterization of Binding Properties of Individual Functional Sites of Human Complement Factor H - Haque, Aftabul; Cortes, Claudio; Alam, M. Nurul; Sreedhar, Maladi; Ferreira, Viviana P.; Pangburn, Michael K. (Frontiers in Immunology, 2020)
Factor H exists as a 155,000 dalton, extended protein composed of twenty small domains which is flexible enough that it folds back on itself. Factor H regulates complement activation through its interactions with C3b and polyanions. Three binding sites for C3b and multiple polyanion binding sites have been identified on Factor H. In intact Factor H these sites appear to act synergistically making their individual contributions difficult to distinguish. Recombinantly expressed fragments of human Factor H were examined using surface plasmon resonance (SPR) for interactions with C3, C3b, iC3b, C3c and C3d. Eleven recombinant proteins of lengths from one to twenty domains were used to show that the three C3b-binding sites exhibit 100-fold different affinities for C3b. The N-terminal site (complement control protein (CCP) domains 1-6) bound C3b with a Kd of 0.08 µM and this interaction was not influenced by the presence or absence of domains 7 and 8. Full length Factor H similarly exhibited a Kd for C3b of 0.1 µM. Unexpectedly, the N-terminal site (CCP 1-6) bound native C3 with a Kd of 0.4 µM. The C-terminal domains (CCP 19-20) exhibited a Kd of 1.7 µM for C3b. We localized a weak third C3b binding site in the CCP 13-15 region with a Kd estimated to be 15 µM. The C-terminal site (CCP 19-20) bound C3b, iC3b and C3d equally well with a Kd of 1 to 2 µM. In order to identify and compare regions of Factor H that interact with polyanions a family of 18 overlapping three domain recombinant proteins spanning the entire length of Factor H were expressed and purified. Immobilized heparin was used as a model polyanion and SPR confirmed the presence of heparin binding sites in CCP 6-8 (Kd 1.2 µM) and in CCP 19-20 (4.9 µM) and suggested the existence of a weak third polyanion binding site in the center of Factor H (CCP 11-13). Our results unveil the relative contributions of different regions of Factor H to its regulation of complement, and may contribute to the understanding of how defects in certain Factor H domains lead to disease.